Ratiometric near-infrared fluorescent probe for nitroreductase activity enables 3D imaging of hypoxic cells within intact tumor spheroids - Morsby, Janeala J; Zhang, Zhumin; Burchett, Alice; Datta, Meenal; Smith, Bradley D (Chemical science (Cambridge), 2024)
Fluorescent molecular probes that report nitroreductase activity have promise as imaging tools to elucidate the biology of hypoxic cells and report the past hypoxic history of biomedical tissue. This study describes the synthesis and validation of a "first-in-class" ratiometric, hydrophilic near-infrared fluorescent molecular probe for imaging hypoxia-induced nitroreductase activity in 2D cell culture monolayers and 3D multicellular tumor spheroids. The probe's molecular structure is charge-balanced and the change in ratiometric signal is based on Förster Resonance Energy Transfer (FRET) from a deep-red, pentamethine cyanine donor dye (Cy5, emits ∼660 nm) to a linked near-infrared, heptamethine cyanine acceptor dye (Cy7, emits ∼780 nm). Enzymatic reduction of a 4-nitrobenzyl group on the Cy7 component induces a large increase in Cy7/Cy5 fluorescence ratio. The deep penetration of near-infrared light enables 3D optical sectioning of intact tumor spheroids, and visualization of individual hypoxic cells ( i.e. , cells with raised Cy7/Cy5 ratio) as a new way to study tumor spheroids. Beyond preclinical imaging, the near-infrared fluorescent molecular probe has high potential for ratiometric imaging of hypoxic tissue in living subjects. A ratiometric, near-infrared fluorescent molecular probe reports nitroreductase activity and enables three-dimensional optical sectioning of intact tumor spheroids with visualization of individual hypoxic cells.